Production of Indigenous Microorganism organic fertilizer and its impact on growth and yield component of Chickpea (Cicer areitinum L.) - Shara Salih Ali (Agricultural Science, 2020)
The aim of this research to improve the productivity of a local variety of chickpea by enriching the soil produced indigenous microorganism (IMO) and reducing the rate of nitrogen fertilizer. The experimental design used in this study was randomized complete block design with three replications. In this research, the soil was enriched with indigenous microorganism with different rates.The treatment combinations were soil with three different rates of IMO (Soil + 0, 2 and 4Tbsp of IMO) .The N fertilizer used in this study was installed in three different rates (0, 30 and 60 ppm NFR) in form of Urea in water) each rate of NFR was measured according to the weight of the soil in the pot. Morphological characters and yield component were determined in this research. The morphological characters included the height of plant, number of branches, days to 50% flowering (days), days to physiological maturity (days) and yield components were: pods number /plant, seed number/plant, seeds weight/plant (g), hundred seed weight (g) and grain yield (kg/ha). The result illustrated that the main effect of IMO gave maximum plant height, number of branches, number of pods/plant, number of seeds/plant, weight of seeds/plant, hundred seeds weight and grain yield. The combination of IMO and NFR under treatment of (Soil + 4Tbsp IMO) with application of 30 ppm NFR also gave highest value of each of morphological characters and yield components. The result of this study demonstrates that enriching soil with 4Tbsp optimize the rate of N fertilizer to 30 ppm.